نظرة في استراتيجيات الخطاب اإلقناعي وعالقتها في األمن الفكري المجتمعي: دراسة استقرائية - Ahmad Mohammad Ahmad Alnadi; Ihab Ahmed Ra'Uf Awais; Rawheya Naim Salem Awad (ARID SCIENTIFIC LTD, 2024)
Non-Indexed Publication